Floral induction (FI) in longan (Dimocarpus longan, Lour.) trees-The possible participation of endogenous hormones. II. Low temperature and potassium chlorate effects on hormone concentrations in and their export out of leaves - K. Sringarm (2018)
Floral induction in longan (Dimocarpus longan Lour.) trees by low temperature (LT) or potassium chlorate (KClO3) treatment, is supposed to act, at least partially, by their interference with the hormonal concentration and/or export out of leaves. Therefore the effect of LT and KClO3on hormone concentration and transport rate of leaves was investigated in these experiments. Results of experiments below show that LT-, but not KClO3, treatment considerably increased the leaf export of N6(Δ2-isopentenyl) adenine/N6(Δ2-isopentenyl) adenosine (iP/iPA) together with indole acetic acid (IAA). Export rates of Zeatin/Zeatin riboside (Z/ZR) and gibberellins (GA) were very low and often below the detection limit (<10 ng). Practically no correlation between the concentrations of IAA, and iP/iPA-type CK of leaves and their export rates out of leaves after LT- or KClO3treatment were observed. This suggests a specific and independent export rate regulation by these two treatments. Potassium chlorate also strongly increased the production of ethylene in leaves. Whether this burst in ethylene is involved in the FI process, or is merely a stress response of the plant against the herbicide KClO3, is unknown but could easily be tested by using inhibitors of ethylene biosynthesis/action. The results of these experiments and their effect on hormonal change and FI in the shoot (results of Part I experiments) are discussed. © 2009.